The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1534/genetics.105.047449
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory cis-trans Evolution and the Dysregulation of Gene Expression in Interspecific Hybrids of Drosophila

Abstract: Hybrids between species are often characterized by novel gene-expression patterns. A recent study on allele-specific gene expression in hybrids between species of Drosophila revealed cases in which cis-and transregulatory elements within species had coevolved in such a way that changes in cis-regulatory elements are compensated by changes in trans-regulatory elements. We hypothesized that such coevolution should often lead to gene misexpression in the hybrid. To test this hypothesis, we estimated allele-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
330
4
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(363 citation statements)
references
References 51 publications
22
330
4
1
Order By: Relevance
“…We have shown in Table 1 that the contribution of interactive terms to expression variation between populations is Ͼ30% and can be as large as 50%. In the analysis of interspecific F 1 hybrids, Landry et al (5) have shown that 13 of the 23 misexpressed genes exhibited cis-bytrans interaction. Furthermore, cis and trans factors can interact in opposition to each other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown in Table 1 that the contribution of interactive terms to expression variation between populations is Ͼ30% and can be as large as 50%. In the analysis of interspecific F 1 hybrids, Landry et al (5) have shown that 13 of the 23 misexpressed genes exhibited cis-bytrans interaction. Furthermore, cis and trans factors can interact in opposition to each other.…”
Section: Discussionmentioning
confidence: 99%
“…(cis regulation refers to the control of expression by the gene itself whereas trans regulation refers to the influence of the genetic background.) Many studies have addressed this question at various levels of divergence (1)(2)(3)(4)(5)(6)(7)(8)(9). For example, one may measure the expressions of two alleles at the locus of interest in a common genetic background (usually F 1 s) (1,2,5).…”
mentioning
confidence: 99%
“…Here, because allelic expression was analyzed in hybrids, only cis-regulatory differences could be detected. In order to detect trans-regulatory effects, it would have been necessary to study allelic expression in not only hybrids but also parental populations at the same life stage, which was not possible here (Wittkopp et al, 2004;Landry et al, 2005;Fraser et al, 2011). We therefore preferred to increase coverage for the hybrid crosses in order to at least more rigorously confirm the occurrence of cis regulation, as directly reflected by significant allelic imbalance in hybrids.…”
Section: Cis-acting Regulatory Effectsmentioning
confidence: 99%
“…For example, dominance in gene expression inheritance has been significantly associated with trans regulatory elements (Lemos et al, 2008). Finally, gene expression regulation can be affected by the interaction of both regulatory systems, either through trans by trans or through cis by trans interactions (Landry et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation